2019
DOI: 10.1002/cpt.1404
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Tamoxifen Metabolism in Patients With Breast Cancer: Preliminary Results of the French PHACS Study

Abstract: In addition to the effect of cytochrome P450 (CYP) 2D6 genetic polymorphisms, the metabolism of tamoxifen may be impacted by other factors with possible consequences on therapeutic outcome (efficacy and toxicity). This analysis focused on the pharmacokinetic (PK)‐pharmacogenetic evaluation of tamoxifen in 730 patients with adjuvant breast cancer included in a prospective multicenter study. Plasma concentrations of tamoxifen and six major metabolites, the genotype for 63 single‐nucleotide polymorphisms, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Both in the present study and in earlier reports 17,21,26 patients with higher concentrations of endoxifen were predominantly carriers of CYP2D6*1. However, a considerable variability among CYP2D6*1 carriers was evident ( Figure 1) and, in analogy with earlier observations, 17,21,26 some patients genotyped as extensive metabolizers were associated with low plasma levels of endoxifen.…”
Section: Discussionsupporting
confidence: 83%
“…Both in the present study and in earlier reports 17,21,26 patients with higher concentrations of endoxifen were predominantly carriers of CYP2D6*1. However, a considerable variability among CYP2D6*1 carriers was evident ( Figure 1) and, in analogy with earlier observations, 17,21,26 some patients genotyped as extensive metabolizers were associated with low plasma levels of endoxifen.…”
Section: Discussionsupporting
confidence: 83%
“…Although CYP2D6 is involved in various tamoxifen metabolic pathways, it is the sole enzyme responsible for the formation of endoxifen from NDM [1]. Previous studies have consistently demonstrated a significant gene-dose effect of CYP2D6 polymorphism for tamoxifen metabolism [3,6,7,8]. Our study also showed an increase in endoxifen concentration and MR E /NDM with increase in CYP2D6 activity score, indicating a gene-dose effect of endoxifen formation.…”
Section: Discussionsupporting
confidence: 71%
“…The bioactivation of tamoxifen involves several CYP450 drug metabolizing enzymes (DMEs) including, CYP2D6, CYP3A4, CYP3A5, CYP2C9, and CYP2C19 , with key roles for CYP2D6 and CYP3A [5]. The wide interindividual variability in the concentration of tamoxifen and its metabolites was mainly attributed to genetic polymorphism in CYP2D6 [3,6,7,8]. Previous studies showed that patients with low CYP2D6 enzyme activity or taking medication which inhibit CYP2D6 activity were associated with lower endoxifen concentration [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] CYP2D6 is especially important for endoxifen formation and patients with impaired or no CYP2D6 activity have shown an increased risk for subtarget C SS,min ENDX . [8][9][10][11] Regarding a putative therapeutic threshold concentration, Madlensky et al reported that patients with C SS,min ENDX < 5.97 ng/mL had a 26% higher breast cancer recurrence rate compared with patients with C SS,min ENDX above this threshold (recurrence rates 16% vs. 10.1-14.7%). 9 This difference is similar to the reported 30% relative reduction in breast cancer recurrence rates, when postmenopausal patients receive aromatase inhibitors instead of tamoxifen.…”
Section: How Might This Change Clinical Pharma-cology or Translationamentioning
confidence: 99%